Designing of Collagen Based Poly(3-hydroxybutyrate-co-4-hydroxybutyrate) Scaffolds for Tissue Engineering - S., Vigneswari; H. P. S., Abdul Khalil; A. A., Amirul (Hindawi Publishing Corporation, 2015)
P(3HB-co-4HB) copolymer was modified using collagen by adapting dual solvent system. The surface properties of samples were characterized by Fourier transforminfrared spectroscopy (FTIR), scanning electron microscopy (SEM), organic elemental analysis (CHN analysis), and water contact angle measurements.The effects of collagen concentration, scaffold thickness, and 4HB molar fraction on the hydrophilicitywere optimized by the Taguchi method.The orthogonal array experiment was conducted to obtain the response for a hydrophilic scaffold. Analysis of variance (ANOVA) was used to determine the significant parameters and determine the optimal level for each parameter. The results also showed that the hydrophilicity of P(3HB-co-4HB)/collagen blend scaffolds increased as the collagen concentration increased up to 15 wt% with a molar fraction of 50mol% at 0.1mm scaffold thickness. The biocompatibility of the P(3HB-co-4HB)/collagen blend surface was evaluated by fibroblast cell (L929) culture.The collagen blend scaffold surfaces showed significant cell adhesion and growth as compared to P(3HB-co-4HB) copolymer scaffolds.